The mediating role of customer satisfaction in the influence of perceived usefulness, perceived ease of use on reuse intention: A study of iSeller POS in Denpasar City - Rifky, Alfriando Muhammad; Setiawan, Putu Yudi (International journal of economic perspectives, 2025)
This study examines the mediating role of customer satisfaction in the relationship between perceived usefulness, perceived ease of use, and reuse intention within the context of point-of-sale (POS) application usage in Indonesia. Grounded in the Technology Acceptance Model (TAM), this research addresses the growing challenge of sustaining post-adoption usage of digital business applications among small and medium-sized enterprises. Despite increasing adoption rates, many POS applications face discontinuance issues after initial implementation, indicating the importance of understanding post-adoption behavior. Using a quantitative explanatory approach, data were collected from POS application users in Denpasar through a structured online questionnaire. A total of valid responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that perceived usefulness and perceived ease of use have significant positive effects on both customer satisfaction and reuse intention. Customer satisfaction is also found to significantly influence reuse intention and partially mediates the relationships between perceived usefulness, perceived ease of use, and reuse intention. These findings contribute to the extension of TAM in a post-adoption context by emphasizing the central role of satisfaction as a psychological mechanism that translates cognitive evaluations into sustained usage behavior. Practically, the study provides insights for digital service providers to enhance user retention by improving system functionality, usability, and overall user experience.